Cabozantinib is well tolerated in acute myeloid leukemia and effectively inhibits the resistance‐conferring FLT3/tyrosine kinase domain/F691 mutation. Issue 2 (28th September 2017) - Fathi, Amir T.; Blonquist, Traci M.; Hernandez, Daniela; Amrein, Philip C.; Ballen, Karen K.; McMasters, Malgorzata; Avigan, David E.; Joyce, Robin; Logan, Emma K.; Hobbs, Gabriela; Brunner, Andrew M.; Joseph, Christelle; et al.
Abstract : BACKGROUND: Cabozantinib, a tyrosine kinase inhibitor of FMS‐like tyrosine kinase 3 (FLT3), MET, AXL, vascular endothelial growth factor receptor, and KIT, is approved for use in multiple malignancies. We assessed the safety and tolerability of cabozantinib in AML, given up‐regulation of multiple relevant pathways. METHODS: Adults were eligible if they were 18 years old or older with relapsed/refractory AML or if they were 70 years old or older with newly diagnosed AML but were ineligible for conventional therapy. Cabozantinib was administered in 28‐day cycles, and dose escalation occurred via cohorts. A pharmacodynamic evaluation of serial plasma samples via a plasma inhibitory assay (PIA) was used to assess FLT3‐inhibitory activity in FLT3‐mutant cell lines. RESULTS: Among 18 patients enrolled, 5 were found to harbor FLT3/ITD mutations. Sixteen patients (89%) had relapsed/refractory AML, and most were treated with 2 or more lines of prior treatment. No dose‐limiting toxicities (DLTs) were detected at the first dose level (40 mg daily), but 2 patients experienced DLTs at the next level (60 mg daily). The remaining patients were then dosed at 40 mg daily, the maximum tolerated dose (MTD). Additional grade 2 or higher toxicities, possibly/probably related to cabozantinib, included fatigue, nausea, transaminitis, and electrolyte imbalance. No patients had a marrow response according to formal criteria, but 4 had peripheral blast reductions; 2 of these 4 patients transiently cleared circulating blasts. One patient experienced a reduction in marrow blasts, and 1 had stable disease. The FLT3‐inhibitory activity of plasma samples, as assessed with the PIA, revealed potent and sustained inhibition in FLT3/ITD and, notably, F691 tyrosine kinase domain (TKD)–mutant cells. CONCLUSIONS: Cabozantinib is well tolerated in AML patients at an MTD of 40 mg daily and is a potent inhibitor of FLT3/ITD‐ and F691 TKD–altered tyrosine kinases. Cancer 2018;124:306‐14. © 2017 American Cancer Society . Abstract : Cabozantinib is well tolerated by patients with acute myeloid leukemia with a maximum tolerated dose of 40 mg daily, and it may have a unique advantage over other FMS‐like tyrosine kinase 3 inhibitors in targeting the F691 tyrosine kinase domain mutation, which is increasingly being seen as a secondary resistance alteration after initial FMS‐like tyrosine kinase 3 inhibitor therapy.